Complications of Percutaneous Coronary Intervention The Survival Handbook - Lindsay, Alistair; Chitkara, Kamal; Di Mario, Carlo (Springer London : Imprint: Springer, 2016)
This book serves as a reference manual for all cardiologists, particularly those in training, who face life-threatening complications of percutaneous coronary intervention (PCI) on a day-to-day basis. From its initial conception, PCI has evolved to become a very complex procedure. Knowledge of what complications can occur during PCI and how to deal with them is vital for the practicing cardiologist, and can mean the difference between life and death. Drawing on the background and experience of an international team of cardiologists, Complications of Percutaneous Coronary Intervention: The Survival Handbook is a valuable, practical, and readable resource for the interventional cardiologist. The principles and practices described within are relevant to all practitioners of interventional catheter procedures, including interventional radiologists, vascular surgeons, and cardiologists.